Produtividade e qualidade da cenoura e microbiota do solo sob adubação verde associada a solarização - Costa, Jacquelinne Alves de Medeiros Araújo (2019)
The association of green manure with soil solarization, besides improving the agronomic characteristics of cultivated plants, especially when spontaneous species such as jitirana and silk flower are incorporated into the soil, allows the control of several pathogens which are not inactivated by solarization when used in isolation, especially when brassicas are used as green manure, as their decomposition release sulfur-rich volatiles and nitrogen-rich compounds, which reduce the potential inoculum of various diseases caused by soil pathogens. Therefore, this work aimed to evaluate the effect of incorporation of plant materials (jitirana, silkworm, castor, cabbage and soil without plant material) associated with soil solarization on carrot production and postharvest quality, as well as as in soil microbial communities. The work was conducted in two seasons (first - June to October 2017; second - September 2017 to January 2018) at Rafael Fernandes Experimental Farm, located in Lagoinha district, Mossoró-RN, using carrot cultivar Brasilia. The following agronomic characteristics were assessed: plant height, stem number per plant, aerial parts and roots’ dry mass, commercial and total carrot yield and classified root yield (long, medium, short and scrap). In addition, the following post-harvest analyzes were performed: firmness; brix; Vitamin C; pH; TA and beta-carotene. Soil samples were collected before and 30 days after incorporation of plant materials for subsequent microbiological analysis of the soil. In addition, the incidence of myeloid geninosis was evaluated. The data obtained were subjected to analysis of variance using the statistical software SISVAR, and the results were compared by the Tukey test at 5%. The joint analysis of the data obtained from the two evaluation periods was also performed. Regarding the effect of incorporation of plant materials, it was observed in the first season that jitirana promoted higher commercial yields (32.85 t ha-1) and total roots (33.30 t ha-1) and lower soluble solids contents (8.85%) and titratable acidity (2.33 mEq/100g). Regarding the effect of fertilization on the soil microbial community, it was found in the first season the castor bean was the plant material that provided the largest amounts of fungi and sporulant bacteria, respectively 3.47x103 and 5.11x105. There was also an increase in total fungi and total bacteria, thirty days after incorporation of plant materials, in both seasons. Significant solarization effect was observed only for beta-carotene content in the two seasons of the experiments. Regarding the time of the experiments, the first season was responsible for the highest yield of carrot roots, both commercial (29.15 t ha-1) and total (29.70 t ha-1), higher firmness, pH and vitamin C, respectively 140.18 N, 6.06 and 3.52 mg/100g, as well as higher amounts of total fungi and total bacteria